2015
DOI: 10.1111/iej.12567
|View full text |Cite
|
Sign up to set email alerts
|

Association between apical periodontitis lesions and plasmatic levels of C‐reactive protein, interleukin 6 and fibrinogen in hypertensive patients

Abstract: The null hypothesis was rejected in favour of the alternative hypothesis. In other words, the presence of chronic apical periodontitis was associated with higher plasmatic levels of CRP, IL-6 and fibrinogen, in a population of severely hypertensive patients. However, the weak association between CAP and each dependent variable suggests a modest participation of endodontic infection on the plasmatic levels of biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…It has also been reported that IL-6 is a potential inducer of addressing molecules on the inflamed vessels [21]. Increased expression of the cytokine in the patients suffering from hypertension and CAD has been reported in the previous investigations [26]. Thus, it seems that IL-6 may be considered as a risk factor for hypertension and CAD.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been reported that IL-6 is a potential inducer of addressing molecules on the inflamed vessels [21]. Increased expression of the cytokine in the patients suffering from hypertension and CAD has been reported in the previous investigations [26]. Thus, it seems that IL-6 may be considered as a risk factor for hypertension and CAD.…”
Section: Discussionmentioning
confidence: 88%
“…High levels of IL-6 in AP seem to be correlated with symptomatic and active lesions [45]. IL-6 is an important pro-inflammatory biomarker and some recent studies aimed to correlate the expression in AP (as a reservoir of inflammatory cytokines) with blood levels in order to verify the relationship of these lesions with systemic inflammatory conditions, showing very conflicting results [3,[47][48][49].…”
Section: Cytokinesmentioning
confidence: 99%
“…11 , 12 Periapical radiolucency due to apical periodontitis may contribute to this problem as it has been reported that apical periodontitis can precipitate a systemic inflammation activation in both healthy persons and patients with a variety of diseases. 13 , 14 However, it remains unknown whether this is also true for cirrhosis patients.…”
Section: Introductionmentioning
confidence: 99%